THE IMPACT OF EXCLUSION ON MINORITIZED LEARNERS: PROMOTING EDUCATIONAL EQUITY AS AN IMPERATIVE FOR SUSTAINABLE DEVELOPMENT - Emmanuel Lucas Nwachukwu; Victoria Azuka Chukwuma; Gift Adaoma Ubani; Godson Chidi Nwokorie; Christopher Chinedu Joseph (CV. Tirta Pustaka Press, 2025)
Despite global advocacy for educational equity, many educational systems continue to inadequately support minoritized learners, particularly those from low-income families and ethnic or racial minority groups, who face systemic barriers such as underrepresentation, economic disparities, discrimination, and unequal access to resources. This study addresses the critical research problem of how exclusionary practices in education limit the potential of marginalized learners and hinder broader social development, highlighting the urgent need for equity-focused interventions. By conducting a systematic literature-based analysis of studies published between 2010 and 2024, this paper identifies recurring patterns of exclusion, effective strategies for fostering inclusivity, and policy gaps that perpetuate educational inequities. Key findings indicate that equity-oriented educational policies—such as targeted resource allocation, culturally responsive curricula, and inclusive pedagogical practices—significantly enhance the academic outcomes, social mobility, and career opportunities of minoritized learners. The study contributes to the discourse on inclusive education by providing evidence-based recommendations for policymakers and educators, demonstrating that sustainable social development is attainable only when educational systems actively prioritize inclusivity and equity. These findings underscore the necessity of comprehensive, systemic reforms to ensure that no learner is left behind, thereby promoting broader societal well-being and reducing inequalities.